Patient-Preferences Favoring Treatment Discontinuation Are Reduced With Vedolizumab and Ustekinumab Compared With TNF Antagonists in Inflammatory Bowel Disease. Issue 4 (29th September 2020) - Kumar, Anand; Kim, Emilie S; Kozan, Philip; Jacob, Vinita; Longman, Randy S; Scherl, Ellen J; Battat, Robert J; Lukin, Dana J
Abstract: Background: Nonadherence to biologic therapy in inflammatory bowel disease (IBD) is associated with risk of relapse, immunogenicity, and disease complications. Significant nonadherence prevalence is reported with tumor necrosis factor (TNF) antagonists but the risk of nonadherence with newer biologics with better safety profiles is unknown. This study aimed to investigate if IBD patient-preferences favoring biologic discontinuation vary by biologic class and analyze factors associated with such preferences. Methods: A convenience sample of 200 adults with IBD on biologic therapy treated at an academic outpatient center was surveyed using a 22-point questionnaire. Patient-preference favoring treatment discontinuation between TNF-antagonist and non-TNF-antagonist biologics [vedolizumab (VDZ)/ustekinumab (UST)] was compared using χ  2 test. Risk factors associated with a preference to discontinue biologic therapy were evaluated using univariable and multivariable logistic regression, and Spearman rank correlation analyses. Results: A total of 190 questionnaires were analyzed that contained data on preferences regarding biologic discontinuation (median age 36 years, 62% were females; 63% had Crohn disease; 56% were receiving a TNF antagonist, 31% VDZ, and 14% UST). Overall, 32% patients reported a preference to discontinue biologic treatment with a higher proportion among those receiving a TNF antagonist compared with VDZ/UST (39.6% vs 21.4%; P < 0.01). Current VDZ/UST use was independently associated with a reduced odds of patient-preference favoring biologic discontinuation [adjusted odds ratio: 2.67 (1.42–5.01); P < 0.01]. The most concerning factor to patients was the perceived risk of side effects. Patients on VDZ/UST perceived their therapy to be safer than those receiving a TNF antagonist ( r = 0.2, P = 0.04). Conclusions: Patient-preference favoring treatment discontinuation is improved with VDZ/UST compared with TNF-antagonist biologic therapy. Lay Summary: Despite several benefits of biologic therapy in inflammatory bowel disease patients, high rates of nonadherence and discontinuation have been reported. This study demonstrates that a significantly lower proportion of patients receiving vedolizumab or ustekinumab compared with tumor necrosis factor-antagonist therapy preferred to discontinue therapy.